Dynamics and diversification of livelihood in urban fringe of Aligarh city, U.P., India - Khan, Nizamuddin; Rehman, Anisur; Salman, Mohd. Sadiq (Journal for Geography, 2012)
Urban fringe is a region of urban-rural interface, continuously moving outward in response to urban sprawl or expansion over the times. It is the area of socio economic transition, experiencing dynamism in the pattern of livelihoods of the people. Land resource used under various cropping systems providing livelihoods to the rural people is declining due to increasing demand of land for non agricultural uses. The declining agricultural activity in the urban fringe has resulted in diversification and structural change in livelihoods. The exposure to urban lifestyle and mass media is causing mental transformation of youth in the urban fringe. They are more inclined towards value added farming systems and non farm activities of secondary or tertiary sectors. Dynamics in socio-economic milieus of urban fringe presented the challenges for livelihood security, employment opportunities and the sustainability of existing farming system and environment in the area. The present study analyzes the impact of urban expansion upon the structural change in pattern of livelihood of people of various socio economic horizons and the diversification of farming systems in the urban fringe of Aligarh city during last 20 years. The study is based on primary data generated through field survey of five villages from urban fringe of the city. The Study reveals expansion of Aligarh city at least three times since 1990. A large number of villages have been included in municipality area but rural economic activities like cropping and animal husbandry still exist in the form of urban vegetable and dairy farming operated by the local people and the immigrants from other parts of the district. The urban fringe witnessed dynamism and diversification in sources of livelihood. The study reveals that approximately 20 percent of surveyed people are only engaged in agriculture. The other important source of livelihood is animal husbandry, agro-processing, retailing and allied services.This structural change in livelihood has resulted in social, economic and environmental instability.